2017 IEEE International Ultrasonics Symposium (IUS) 2017
DOI: 10.1109/ultsym.2017.8092412
|View full text |Cite
|
Sign up to set email alerts
|

Elevation resolution enhancement in 3D photoacoustic imaging using FDMAS beamforming

Abstract: Abstract-Photoacoustic imaging is a non-invasive and nonionizing imaging technique that combines the spectral selectivity of laser excitation with the high resolution of ultrasound imaging. It is possible to identity the vascular structure of the cancerous tissue using this imaging modality. However, elevation and lateral resolution of photoacoustic imaging is usually poor for imaging target. In this study, three dimension filter delay multiply and sum beamforming technique (FDMAS(3D)) is used to improve the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Alshaya et al reported another algorithm named the 36 Filter Delay Multiply and Sum (FDMAS) beamforming technique, which is an adaptive beamforming technique that depends on the autocorrelation between delayed radio frequency (RF) data. Due to the autocorrelation operation, the FDMAS beamforming technique cannot be applied directly in 3D PAI.…”
Section: Imaging Algorithms For Improving the Elevation Resolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alshaya et al reported another algorithm named the 36 Filter Delay Multiply and Sum (FDMAS) beamforming technique, which is an adaptive beamforming technique that depends on the autocorrelation between delayed radio frequency (RF) data. Due to the autocorrelation operation, the FDMAS beamforming technique cannot be applied directly in 3D PAI.…”
Section: Imaging Algorithms For Improving the Elevation Resolutionmentioning
confidence: 99%
“…Liu et al designed and built a handheld, real-time PAI system with manually adjustable side light delivery. 41 To optimize the laser light delivery, ā nite element simulation was employed to evaluate the in°uence of the incident angle and interval 35 One translational scan Fast No Medium FDMAS 36 One translational scan Fast No Medium between the two arms of the¯ber bundle regarding light°uence. Phantom experimental validations were performed and the results were consistent with the simulations results.…”
Section: Adjustable Side Light Deliverymentioning
confidence: 99%